Building Organizational Citizenship Behavior through Authentic Leadership and Organizational Commitment - Amran, Ali (Journal of International Conference Proceedings, 2023)
Leaders and employees are valuable human resources in a company. Proper leadership accompanied by employee commitment is needed for the organizationâ€™s sustainability. This research seeks to ascertain the influence of authentic leadership and organizational commitment on organizational citizenship behavior. Survey method with descriptive and verificative research was used to obtain the data by using are primary data obtained from the distribution of questionnaires. Saturated Sampling is the method of sampling that is used.. The samples involved were 97 respondents, namely employees at PT Aneka Produksi Nusajaya. The results showed that organizational citizenship behavior was positively and significantly influenced by organizational commitment and authentic leadership , either partially or concurrently. In addition, variable of authentic leadership have a greater influence on organizational citizenship behavior than variable of organizational commitment. This research findings are expected to be used by companies to build organizational citizenship behavior through aspects of authentic leadership and organizational commitment.Â